2016
DOI: 10.1111/ecc.12558
|View full text |Cite
|
Sign up to set email alerts
|

Needs of adolescents and young adults after cancer treatment: a systematic review

Abstract: The aim of this study was to conduct a systematic review of the literature on the needs of adolescents and young adults (AYAs) who have survived cancer. PRISMA recommendations for systematic reviews were followed, and the quality of the studies reviewed was also assessed with a specific checklist. The following databases were searched from their inception to May 2016: ERIC, EMBASE, MEDLINE, PILOTS, ProQuest, PsycARTICLES, PsycBOOKS, psycCRITIQUES, PsycINFO, Social Services Abstracts and Sociological Abstracts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 39 publications
0
53
1
1
Order By: Relevance
“…Counseling and psychological support are among the most common needs expressed by these survivors, 33 who often report symptoms of posttraumatic stress, anxiety and depression, and fears of cancer recurrence. More than 40% of survivors had at least 1 visit, and 90% of encounters were with family physicians and psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counseling and psychological support are among the most common needs expressed by these survivors, 33 who often report symptoms of posttraumatic stress, anxiety and depression, and fears of cancer recurrence. More than 40% of survivors had at least 1 visit, and 90% of encounters were with family physicians and psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that adolescents are vulnerable to psychological challenges after a cancer diagnosis. Counseling and psychological support are among the most common needs expressed by these survivors, 33 who often report symptoms of posttraumatic stress, anxiety and depression, and fears of cancer recurrence. 34 Many adolescents who require mental health services after cancer do not receive them, 35,36 suggesting that the documented rate of visits underestimates their true burden of psychological morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have focused on the experiences of AYA survivors or caregivers with mixed cancer diagnoses. 8,9 Other reviews have concentrated on the experiences of children, 10,11 adults, 12 or caregivers of adult brain tumour survivors. 13 To date, no systematic review has collated evidence on the experiences of AYA childhood brain tumour survivors and/or their caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis also revealed, as expected, a significant and positive association between fatigue and pain interference in daily activities. Fatigue is known to be a common problem in both cancer patients (Bower, 2019;Kolak et al, 2017) and cancer survivors (Galán, De la Vega, & Miró, 2018;Galán et al, 2017), and the ob- Similarly, pain catastrophising was found to contribute to the explanation of pain interference with daily activities. This is consistent with the results of previous studies in other patient populations.…”
Section: Discussionmentioning
confidence: 99%